Fe3+ doped amorphous Co2BOy(OH)z with enhanced activity for oxygen evolution reaction. (1st August 2018) - Xue, Chenglin; Li, Guangshe; Wang, Jianghao; Wang, Yan; Li, Liping
Abstract: Achieving efficient oxygen evolution reaction (OER) is crucial for advancing energy storage and conversion technologies. Several methodologies have been developed to expedite the OER process. However, producing catalysts with excellent performance still remains challenging. Herein, we successfully achieve an enhanced OER performance in amorphous (Co1-x Fex )2 BOy (OH)z (x = 0, 10, 20, 30, 40 and 50%) by improving electrode kinetics. The incorporation of Fe 3+ not only improves the charge transfer rate, but also modulates the absorption ability of Fe 3+ ions to hydroxyl, as evidenced by the decrease of 3d electron density from the Mössbauer measurement. As a consequence, (Co0.7 Fe0.3 )2 BOy (OH)z shows a superior electrocatalytic performance with a current density of 10 mA cm -2  at an overpotential of 308 mV and a Tafel slope of 39 mV dec −1, which are smaller than those observed for undoped parent catalyst Co2 BOy (OH)z and commercial IrO2. Moreover, (Co0.7 Fe0.3 )2 BOy (OH)z catalyst has a high stability in OER electrocatalytic process. The current density still remains about 70% after continuous electrocatalytic reaction for 12 h. (Co0.7 Fe0.3 )2 BOy (OH)z used as anode also catalyzes overall water splitting reaction to give a current density of 20 mA cm -2  at 1.62 V when taking Pt/C catalyst as cathode. The present study provides an effective approach to design new metal-based electrocatalystsby introducing foreign cation to alter outer electron density and further modulating the electrochemical activity. Highlights: Series of (Co1-x Fex )2 BOy (OH)z catalysts were prepared by a facile oxidation-reduction method. The optimized (Co0.7 Fe0.3 )2 BOy (OH)z exhibited superior OER activity and durability. A reduced 3d-electron density in (Co0.7 Fe0.3 )2 BOy (OH)z was found by the 57 Fe Mössbauer spectrum. Correlation between Fe 3+ and OER activity was established. (Co0.7 Fe0.3 )2 BOy (OH)z catalyzed water splitting to give a current density of 20 mA cm -2  at 1.62 V.